Effectiveness of the Sanofi/GSK (VidPrevtyn Beta) and Pfizer-BioNTech (Comirnaty Original/Omicron BA.4-5) bivalent vaccines against hospitalisation in EnglandResearch in context - Freja Cordelia Møller Kirsebom; Nick Andrews; Julia Stowe; Gavin Dabrera; Mary Ramsay; Jamie Lopez Bernal (EClinicalMedicine, 2024)
Summary: Background: The Sanofi/GSK AS03-adjuvanted (VidPrevtyn Beta) vaccine and the Pfizer-BioNTech mRNA (Comirnaty Original/Omicron BA.4-5) bivalent vaccine were offered to adults aged 75 years and over in England from 3rd April 2023. This is the first time an adjuvanted COVID-19 vaccine has been administered as part of a UK COVID-19 vaccination programme. In clinical trials, antibody levels generated were comparable with mRNA vaccines but there are no real-world data on the effectiveness or duration of protection. Methods: We used a test-negative case–control study design to estimate the incremental vaccine effectiveness of the Sanofi/GSK and Pfizer bivalent BA.4-5 boosters against hospitalisation amongst those aged 75 years and older in England. Cases (those testing positive) and controls (those testing negative) were identified from the national COVID-19 PCR testing data undertaken in hospital settings. The study period included tests from 3rd April 2023 to 27th August 2023. Tests were linked to the COVID-19 vaccination register and to the national hospital admission database, restricting to those with an acute respiratory infection coded in the primary diagnosis field. Vaccine effectiveness was estimated using multivariable logistic regression amongst those who had last received an autumn 2022 booster given at least 3 months prior. The test result was the outcome and vaccination status the exposure. Analyses were adjusted for week of test, gender, age, clinical risk group status, care home resident status, region, index of multiple deprivation, ethnicity, influenza vaccination status and recent COVID-19 positivity. Findings: There were 14,169 eligible tests from hospitalised individuals aged 75 years and older; 3005 cases (positive tests) and 11,164 controls (negative tests). Effectiveness was highest in the period 9–13 days post vaccination for both manufacturers at about 50%; 43.7% (95% CI, 20.1–60.3%) and 56.1% (95% CI, 25.2–74.2%) for Sanofi/GSK and Pfizer BA.4-5, respectively. There was evidence of waning with a reduction to about 30% for both manufacturers after 5–9 weeks. The longest time interval post vaccination for which we were able to estimate effectiveness was 10+ weeks post vaccination, at which point vaccine effectiveness was 17.6% (95% CI, −3.6 to 34.5%) and 37.9% (95% CI, 13.2–55.5%) for the Sanofi/GSK and Pfizer BA.4-5 boosters, respectively. Interpretation: Both boosters provided good protection against hospitalisation amongst older adults. The finding that the adjuvanted vaccine targeting the distant Beta strain had similar effectiveness to the bivalent mRNA vaccine targeting more closely matched Omicron sub-lineages is notable and highlights the need for further real-world studies into the effectiveness of vaccines from different vaccine platforms and formulations in the presence of matched and unmatched strains. Funding: No external funding.